(untitled) (Iraqi Journal of Medical Sciences, 2024)
Background: Diabetes-related nephropathy DN is a form of renal impairment that affects 40 % of DM patients. It is a permanent state that leads to inflammation and affects a large number of diabetes patients worldwide. Netrin-1 (NTN-1) is a protein that belongs to a group of proteins called neuronal guidance proteins and has a significant impact on the regulation of inflammation by impacting the migration of cells. Objective: To assess the relation of serum NTN-1 level with the early detection of nephropathy in type 2 diabetes mellitus (T2DM) patients. Methods: A total of 88 individuals were enrolled in this cross-sectional study, and subdivided into three groups: normoalbuminuria, microalbuminuria, and macroalbuminuria. Serum NTN-1 was measured by using an enzyme-linked immunosorbent test (ELISA). Results: The DN patients had significantly different serum levels of NTN-1; the macroalbuminuria group had the greatest value (1127.73±407.93 pg/ml). The prediction of DN was determined by ROC curve analysis to have 88% sensitivity and 63% specificity for serum netrin-1 at a cutoff point of 686.5 pg/ml with an AUC of 0.642 (P = 0.08). Conclusion: There is a progressive increase in serum NTN-1 levels with the severity of albuminuria in T2DM patients. Keywords: Netrin-1; Biomarkers, diabetic nephropathy, type 2 diabetes mellitus, albuminuria Citation: Abdulfattah SW, Abdulsattar SA, Rahmah AM. Serum Netrin-1 level in type 2 diabetic nephropathy. Iraqi JMS. 2024; 22(2): 252-258. doi: 10.22578/IJMS.22.2.9